Key component of inflammasome, NLRC4, was identified in the lesional epidermis of psoriatic patients. Issue 8 (24th May 2018) - Hiruma, Junichiro; Harada, Kazutoshi; Motoyama, Akira; Okubo, Yukari; Maeda, Tatsuo; Yamamoto, Mami; Miyai, Masashi; Hibino, Toshihiko; Tsuboi, Ryoji
Abstract: Inflammasomes are multimolecular complexes that control the inflammatory response. The function of inflammasomes in the pathogenesis of psoriasis is still unclear. To clarify the relationship between inflammasomes and the pathophysiology of psoriasis, and in particular, to identify molecules interacting with caspase‐1, a crucial component of inflammasomes, scale extracts obtained from patients with psoriasis were immunoprecipitated with anti‐caspase‐1 antibody and analyzed by liquid chromatography coupled with electrospray tandem mass spectrometry (LC‐MS/MS). The expression of the inflammasome component was assessed by immunohistochemical analysis and an in vitro assay. We identified several candidates for caspase‐1‐interacting proteins from the psoriatic scale extracts by immunoprecipitation and LC‐MS/MS. Nucleotide‐binding oligomerization domain‐containing protein‐like receptor family CARD domain‐containing protein 4 (NLRC4) was the only inflammasome component among the candidates; thus, the protein is considered to be a key factor of inflammasomes in psoriasis. No inflammasome component was found in the extracts of atopic dermatitis or normal skin by LC‐MS/MS. Immunohistochemical analysis demonstrated upregulation of NLRC4 in the lesional epidermis of some psoriatic patients whereas weak expression of NLRC4 was detected in the normal and non‐lesional epidermis. The mRNA expression of the NLRC4 gene increased in keratinocytes at confluency, 48 h after air exposure and after the addition of 1.5 mmol/L calcium chloride. Our findings suggest that NLRC4 may be involved in the exacerbation or modification of psoriatic lesions.